2018
DOI: 10.1016/s1474-4422(18)30232-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of TREM2 in Alzheimer's disease and other neurodegenerative disorders

Abstract: Alzheimer's disease is a genetically complex disorder; rare variants in the triggering receptor expressed on myeloid cells 2 (TREM2) gene have been shown to as much as triple an individual's risk of developing Alzheimer's disease. TREM2 is a transmembrane receptor expressed in cells of the myeloid lineage, and its association with Alzheimer's disease supports the involvement of immune and inflammatory pathways in the cause of the disease, rather than as a consequence of the disease. TREM2 variants associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
144
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(166 citation statements)
references
References 101 publications
(173 reference statements)
6
144
0
Order By: Relevance
“…Based on accumulating evidence from recent studies, a reduction in the activity of the TREM2 signalling pathway promotes neurodegeneration. 30,48 Because brain Aβ42 levels were comparable in App NL-F/wt knock-in mice and App NL-F/wt knock-in; ob/ob mice, soluble Aβ42 might not be targeted by microglia. Rather, the dysregulation of microglia may cause susceptibility to Aβ.…”
Section: Discussionmentioning
confidence: 99%
“…Based on accumulating evidence from recent studies, a reduction in the activity of the TREM2 signalling pathway promotes neurodegeneration. 30,48 Because brain Aβ42 levels were comparable in App NL-F/wt knock-in mice and App NL-F/wt knock-in; ob/ob mice, soluble Aβ42 might not be targeted by microglia. Rather, the dysregulation of microglia may cause susceptibility to Aβ.…”
Section: Discussionmentioning
confidence: 99%
“…It was then that a pair of reports published back-to-back detailed findings that a rare SNP in TREM2 (resulting in amino acid change R47H) altered AD risk with the highest odds ratio of any AD risk gene outside of APOE (Figure 1) (Guerreiro et al, 2013a;Jonsson et al, 2013). More recent analysis has found an additional SNP variant in TREM2 that also reached statistical significance (R62H; (Sims et al, 2017)), and several other variants are more prevalent in AD patients than controls but have yet to reach significance or be replicated, likely in part due to their scarcity in the population (Carmona et al, 2018). In addition, homozygous TREM2 variants were also found to be casual for a form of FTD (Carmona et al, 2018;Chouery et al, 2008;Guerreiro et al, 2013a), while other variants significantly elevated FTD risk (Carmona et al, 2018;Giraldo et al, 2013).…”
Section: Trem2 Signaling Networkmentioning
confidence: 97%
“…Like DLB, the genetics of FTD is still a new field, however several studies have still identified links between FTD genetics and altered immune function and signaling (Broce et al, 2018;Carmona et al, 2018;Pottier et al, 2019). As previously discussed, the study of FTD is complicated by the significant pathological and clinical heterogeneity of the disorder.…”
Section: Evidence From Human Genetics Highlights Immunementioning
confidence: 99%
See 1 more Smart Citation
“…Genome wide association studies (GWAS) identify a number of coding variants highly expressed in microglia 12 . Of the GWAS identified risk factors, cluster of differentiation (CD) 33 and triggering receptor expressed on myeloid cells 2 (TREM2) have been shown to be involved in phagocytosis and response to stimuli when further examined both in vitro and in vivo 4,13,14 . Microglia harvested from aged dual amyloid precursor protein/presenilin 1 (APP swe PS1 ΔE9 ) model of AD also show decreased expression of Aβ binding receptors and Aβ degrading enzymes 15 .Similar to microglia, the type-I interferon (IFN) cytokine family are also critical in neuroinflammation.…”
mentioning
confidence: 99%